La lectura del paisaje: semiótica del color y la forma en «Giappone» de Collezione di Sabbia de Italo Calvino - Barrado Belmar, Mari Carmen (Cuadernos de Filología Italiana, 2007)
The landscape is liable of being read and interpreted. As landscape we understand the set formed by the architecture, the vegetation, the industrial facilities and the human beings who are part of it. All of them are senders of decipherable messages, all of them become culture and, as Eco points out, Tutta la cultura deve essere studiata come un fenomeno di comunicazione. Calvino, as we will see in one of the texts, says: Penso: ecco che il paesaggio mi ha dettato il tema per una poesia. In this study we devote ourselves to collecting and extracting data about the semiotic value of the shape and the colour that are manifested in the landscape.